TREATMENT PROFILE AND SURVIVAL ANALYSIS ACUTE RESPIRATORY DISTRESS SYNDROME (ARDS) COVID-19 PATIENTS - MICHAEL; RAMATILLAH, DIANA LAILA (International Journal of Applied Pharmaceutics, 2022)
Objective of the review was to evaluate the correlation between treatment profile and survival analysis among Acute Respiratory Distress Syndrome (ARDS) covid-19 patients. Journals were searched from Google scholar, Elsevier and Pubmed with references from 2018 to 2021. Hydroxychloroquine and favipiravir has a good outcome in treating severe to critical illness patients. Ivermectin has a better output on treating mild to moderate symptoms covid-19 but further study is required to know the outcome from treating severe to critical illness. Oseltamivir only works on mild cases of covid-19, early-onset therapy on patient covid-19 can reduce the time of fever. An antibacterial is applied on the covid-19 patients with pneumonia and for cytokine storm patients required tocilizumab on therapy. Severe to critical cases of covid-19 can be given corticosteroid. Lopinavir/ritonavir and ribavirin have a poor antiviral activity against SARS-CoV-2. In conclusion, for severe to critical illness required hydroxychloroquine or favipiravir as antiviral agent plus antibacterial agent, if cytokine storm is developed tocilizumab can be given. For mild to moderate symptoms can be given oseltamivir or ivermectin, if there is a sign of bacterial infection (pneumonia) an antibacterial agent can be given.